Risk Stratification of Latent Tuberculosis Defined by Combined Interferon Gamma Release Assays - Corbière, Véronique; Pottier, Gaelle; Bonkain, Florence; Schepers, Kinda; Verscheure, Virginie; Lecher, Sophie; Doherty, T. Mark; Locht, Camille; Mascart, Françoise (PLOS ONE, 2012)
Background Most individuals infected with Mycobacterium tuberculosis develop latent tuberculosis infection (LTBI). Some may progress to active disease and would benefit from preventive treatment yet no means currently exists to predict who will reactivate. Here, we provide an approach to stratify LTBI based on IFN-γ responses to two antigens, the recombinant Early-Secreted Antigen Target-6 (rESAT-6) and the latency antigen Heparin-Binding Haemagglutinin (HBHA). Methods We retrospectively analyzed results from in-house IFN-γ-release assays with HBHA (HBHA-IGRA) and rESAT-6 (rESAT-6-IGRA) performed during a 12-year period on serial blood samples (3 to 9) collected from 23 LTBI subjects in a low-TB incidence country. Both the kinetics of the absolute IFN-γ concentrations secreted in response to each antigen and the dynamics of HBHA/rESAT-6-induced IFN-γ concentrations ratios were examined. Results This analysis allowed the identification among the LTBI subjects of three major groups. Group A featured stable HBHA and rESAT-6-IGRA profiles with an HBHA/rESAT-6 ratio persistently higher than 1, and with high HBHA- and usually negative rESAT-6-IGRA responses throughout the study. Group B had changing HBHA/rESAT-6 ratios fluctuating from 0.0001 to 10,000, with both HBHA and rESAT-6 responses varying over time at least once during the follow-up. Group C was characterized by a progressive disappearance of all responses. Conclusions By combining the measures of IFN-γ concentrations secreted in response to an early and a latency antigens, LTBI subjects can be stratified into different risk groups. We propose that disappearing responses indicate cure, that persistent responses to HBHA with HBHA/rESAT-6 ratios ≥1 represent stable LTBI subjects, whereas subjects with ratios varying from >1 to <1 should be closely monitored as they may represent the highest-risk group, as illustrated by a case report, and should therefore be prioritized for preventive treatment.